Problems of Implementing the Independent Learning Curriculum in the Digital Era - Satriani; Amiruddin; Sakinah, Andi; Muktamar, Ahmad (ETDC: Indonesian Journal of Research and Educational Review, 2023)
The use of technology and new approaches to learning is essential to facing the current digital era. This study aims to explore the challenges and opportunities of implementing this approach at the As'Adiyah Sengkang Islamic Institute, with a focus on the impact of digital transformation. This research used mixed methods, including surveys, interviews, focus groups, and document analysis. Data was collected from students, lecturers, and administrative staff to gain comprehensive insight into the challenges faced during the transition to independent learning in a digital environment. The research results identified a number of crucial challenges, namely limited technological infrastructure, lecturers' readiness to use technology, student motivation and independence, evaluation and assessment, and a lack of social interaction and collaboration. The discussion emphasized the importance of addressing these challenges through targeted strategies, including improving technological infrastructure, training and development of lecturers, promoting student motivation, more contextual assessment, facilitating social interaction and collaboration, and continuous evaluation and improvement. This is the key to the successful implementation of the Independent Learning Curriculum in the digital era at the As'Adiyah Sengkang Islamic Institute. This research provides valuable insight into the complexity of educational transformation in the digital era and provides guidance for higher education institutions facing similar transitions.